Representation and reasoning of fuzzy temporal knowledge - Nor Azlinayati Abdul Manaf; Mohammad Reza Beikzadeh (IEEE Xplore, 2006)
This paper proposes a model for fuzzy temporal knowledge representation and reasoning. It includes the frameworks that incorporate fuzziness with temporal intervals, representation of the knowledge and reasoning qualitatively and quantitatively. An interval-based fuzzy membership representation is defined as an extension to the precise temporal interval. To deal with planning and scheduling in this framework, a simple decision problem is shown.